A high-salt diet aggravates retinal ischaemia/reperfusion injury. (November 2019) - Li, Qingchen; Fang, Wangyi; Hu, Fangyuan; Zhou, Xujiao; Cheng, Yun; Jiang, Chunhui
Abstract: Ischaemia/reperfusion contributes to the pathophysiological process of many retinal diseases. Previous studies have shown that retinal ischaemia/reperfusion mainly results in neuronal degeneration, including thinning of the retina, retinal ganglion cell death and reductions in electroretinography. A high-salt diet contributes to the inflammatory response and tissue hypoperfusion and may be associated with ischaemia/reperfusion injury. In the present study, we investigated the influence of a high-salt diet on retinal ischaemia/reperfusion injury and explored the potential mechanism in a rat model. The results revealed that the high-salt diet aggravated ischaemia/reperfusion-induced thinning of the retina. A TUNEL assay and Brn-3a staining revealed substantially more severe cell death and loss of retinal ganglion cells, and electroretinography confirmed worse retinal function in the ischaemia/reperfusion eyes of rats fed the high-salt diet. These effects may be associated with upregulation of Caspase-3, Bax, Interleukin-1β and Interleukin-6 and decreased expression of nitric oxide. In summary, a high-salt diet aggravates ischaemia/reperfusion-induced retinal neuronal impairment by activating pro-apoptotic and pro-inflammatory signalling pathways and inhibiting vasodilation. Highlights: High salt diet is found for the first time to aggravate the neuronal degeneration induced by ischaemia/reperfusion in retina. Excess salt promotes pro-apoptotic proteins and pro-inflammatory cytokines in retina after ischaemic insult. Excess salt inhibits the release of NO and might deteriorate ischaemia/reperfusion injury via blunting retinal vasodilation.